(3LegQI GdCfSGHs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3bQjT cdgG ef hdO agO Hf eGdc s
(3BNQgG (B:s
(3GfbVi GdcdGe ajge hGdMeO ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B115 - (3U(B199s
(3GdehLhO bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B107 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B605s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK (B((3)2114) s
Keywords: (3GdJGQjNs